Comparison of anxiety levels of hospitalized COVID‐19 patients, individuals under quarantine, and individuals in society. Issue 1 (20th May 2021) - Tokur Kesgin, Makbule; Hançer Tok, Hümeyra; Uzun, Lütfiye N.; Pehlivan, Şenay
Abstract: Purpose: This study aims to compare the anxiety levels of COVID‐19 patients, individuals under quarantine, and healthy individuals in society. Design and Methods: This cross‐sectional study was conducted from May 25, 2020 to June 25, 2020 in a city located in the northwest of Turkey. The data were collected using a personal information form, the Beck Anxiety Scale, administered in face‐to‐face interviews, and online questionnaires. The data were analyzed using descriptive statistics, Kruskal–Wallis, Mann–Whitney U, and logistic regression analyses. Findings: The anxiety level of individuals under quarantine (Median: min–max = 1: 0–55) was significantly lower statistically compared to that of the rest of the society (Median: min–max = 6: 0–63) and hospitalized COVID‐19 patients (Median: min–max = 5: 0–42) ( p  = 0.0001). Female gender, being 61 years of age and older, having psychiatric and chronic illnesses, and experiencing disrupted sleep patterns were determined to be the factors associated with high levels of anxiety. Practice Implications: This study found that society in general and hospitalized COVID‐19 patients had high anxiety levels. The study results can be useful for creating training and population‐based screening programs to control the anxiety of individuals under quarantine, hospitalized COVID‐19 patients, and the rest of the society during the pandemic. Additionally, the finding from this study on groups at risk for anxiety will provide important data for future research on this subject and for the planning of health services offered to these groups.